Dinamika Kepentingan Dalam Program “Kampung Keren” (Kreatif Dan Independen) Sebagai Strategi Branding Kota Kediri - Ningtyas, Trimurti; Alamin, Taufik; Saifu Rijal, Mohammad Hasan (Universitas Dr. Soetomo Surabaya, 2024)
Branding is an unavoidable necessity in the development of urban areas and population. Kampung Keren is one of the branding strategies carried out by the Kediri city government in improving the image of the city of Kediri. The growing awareness and independence of the community in managing their territory is the main goal in implementing this Kampung Keren. In fact, the existence of Kampung Keren cannot be used as a program that is successfully implemented by looking at the economic and social developments in the City of Kediri. This study aims to explore the dynamics of interest in the implementation of Kampung Keren as a branding strategy in the City of Kediri. Researchers explored information through the managers of 7 (seven) Kampung Keren in Kediri City and collected documentation related to Kampung Keren in government agencies and made observations on the process of implementing Kampung Keren. As a result, there are various obstacles faced by the community, managers and the government of the City of Kediri in developing 6 Kampung Keren points. Limited human and capital resources are the main problem in its implementation. Apart from that, other results show that there is political interest through this branding which is a polemic itself. The existence of conflicting interests of the actors involved is a separate obstacle in its implementation. This unpreparedness is an obstacle that must be resolved, so that Kampung Keren can optimally and increase efforts to develop urban areas and population through Branding in the City of Kediri.